1999
DOI: 10.1128/cdli.6.6.844-850.1999
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Endotoxin-Binding Proteins during Major Elective Surgery: Important Role for Soluble CD14 in Regulation of Biological Activity of Systemic Endotoxin

Abstract: Assessment of circulating endotoxin during the perioperative period, which is only demonstrated by the Limulus amebocyte lysate (LAL) test, may be modulated by several endotoxin-binding proteins. Endotoxin-neutralizing capacity (ENC) and the plasma levels of soluble CD14 (sCD14), lipopolysaccharide-binding protein, and bactericidal/permeability-increasing protein (BPI) were determined in 40 patients 6 h prior to skin incision for major abdominal surgery. The bioactivity of plasma endotoxin was tested by the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 50 publications
3
9
0
2
Order By: Relevance
“…The serum level of sCD14 was inversely correlated with the serum level of LPS in our study. This finding can possibly be explained by a loss of sCD14 from consumption by LPS reaching the bloodstream as showed before by Hiki et al . Funderburg et al .…”
Section: Discussionsupporting
confidence: 69%
“…The serum level of sCD14 was inversely correlated with the serum level of LPS in our study. This finding can possibly be explained by a loss of sCD14 from consumption by LPS reaching the bloodstream as showed before by Hiki et al . Funderburg et al .…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have demonstrated that loss of gut barrier function together with bacterial and endotoxin translocation might be major causes of postoperative acute‐phase reactions after abdominal surgery17–19. In the present study, only animals in the open group showed significant portal and systemic endotoxaemia after gastrectomy.…”
Section: Discussionsupporting
confidence: 44%
“…Small‐bowel manipulation during abdominal surgery can initiate an intense local inflammatory response12–15 and cause distant organ damage16. Previous studies have demonstrated that loss of gut barrier function together with bacterial and endotoxin translocation might be the major cause of postoperative acute‐phase reactions after abdominal surgery17–19. Surgical manipulation during laparoscopic procedures causes only minor trauma to the peritoneal environment and this could minimize the inflammatory response in the gut that results in bacterial or endotoxin translocation.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we determine plasma sCD14 and LBP rather than plasma endotoxin considering the short half-life of plasma LPS in humans (about 3 hours), compared with those of sCD14 and LBP (24-48 h), that indicates that plasma sCD14 and LBP probably reflect long-term LPS exposure while plasma LPS could reflect the transient kinetics of LPS absorption only. In agreement with this, the release of sCD14 by cultured peripheral blood monocytes has been shown to increase significantly in the presence of low stimulatory LPS concentrations (0.01 ng/ml), suggesting that sCD14 may be considered as a biomarker of LPS exposure [44,45]. Our results show that the synbiotic treatment did not improve the plasma concentrations of usCRP, IL-6 and LBP while it contributes to maintain lower plasma concentrations of sCD14 during the study compared with the control group.…”
Section: Discussionmentioning
confidence: 52%